Q. Septimi Florentis Tertulliani Apologeticus : The Text of Oehler, Annotated, with an Introduction - Tertullian, approximately 160-approximately 230 (Cambridge library collection. Religion., 1917)
A masterpiece of rhetoric and an impassioned defence of faith in the face of persecution, this work represents a key work in the Latin patristic canon. Addressing the magistrates of the Roman court, Tertullian submits 'the real facts in the case of the Christians', defending the legitimacy of the new faith while charging its detractors with hypocrisy and worse. Scathing, eloquent and defiant, the Apology demonstrates the importance of classical rhetoric to the identity of the controversial religion and its recent converts. This edition (1917), accompanied by a complete commentary by J. E. B. Mayor and translation by Alexander Souter, has been called 'by the far the best commentary ever published' on the work. Published posthumously from Mayor's extensive Cambridge lecture notes, the commentary is a starting point for anyone seeking a full understanding of the text's critical history. Souter's English translation makes it accessible to experts and non-experts alike.